ПРОБЛЕМИ ІДЕНТИФІКАЦІЇ ОСОБИСТОСТІ В ІНФОРМАЦІЙНОМУ СУСПІЛЬСТВІ - Жидкова, О. О. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Аналізуються проблеми ідентифікації особистості, викликані змінам в засобах інформаційної техніки. Особлива увага приділяється розгляду інформаційних технологій, які не лише змінили управління технологічними процесами, але і стали інструментом впливу на діяльність людини. О.О. Жидкова ПРОБЛЕМЫ ИДЕНТИФИКАЦИИ ЛИЧНОСТИ В ИНФОРМАЦИОННОМ ОБЩЕСТВЕ Анализируются проблемы идентификации личности, вызванные изменениями, вносимыми средствами информационной техники. Особенное внимание уделяется рассмотрению информационных технологий, которые не только изменили управление технологическими процессами, но и стали инструментом воздействия на деятельность человека. Ключевые слова: информационное общество, информационные технологии, виртуальная реальность, коммуникативная среда, техносфера, идентификация, самоидентификация. O. Zhidkova PROBLEM IDENTIFICATION OF PERSONALITY IN THE INFORMATION SOCIETY The problems of identification, due to changes introduced by means of information technology. Particular attention is paid to the information technology, which not only changed the management of technological processes, but also became the instrument of influence on human activities. Key words: information society, information technology, virtual reality, communication environment, a technosphere, identification, self-identification.